How do you integrate int (sinx) / ((cos^2x + cosx -2)) dx using partial fractions?

1 Answer
Dec 16, 2015

1/3 ln|(cos x + 2)/(cos x - 1)|

Explanation:

When dealing with trigonometric functions during partial fraction expansions, it can be very helpful to make some substitutions to simplify the problem. We will let u = cosx. Then we have

int sin x /(cos^2 x + cos x - 2)dx = int sin x / (u^2 + u - 2) dx

We may actually take this one step further and eliminate the sin from the numerator. In this case we will note that (du)/(dx) = -sin x.

One can think of this as being equivalent to -du = sin x dx.

After replacing sin x dx with -du we have

int sin x / (u^2 + u - 2) dx = int (-du) / (u^2 + u - 2)

Now we can simply expand our new, trig-less expression and integrate normally.

We will factor the denominator, and set the expression equal to a general expression involving these factors to begin the partial fraction expansion:

-1/((u + 2)(u - 1)) = A/(u + 2) + B/(u - 1)

To continue our expansion we will multiply through by (u + 2)(u - 1) as follows,

-1 = A(u - 1) + B(u + 2) = Au - A + Bu + 2B

We may now find A and B by equating coefficients. To show more clearly what we're working with, I'll rearrange everything a bit:

-1 = (A + B)u + (2B - A)

On the left-hand side, we have no multiples of u. Thus, A + B must equal zero. 2B - A then must equal -1.

A + B = 0
2B - A = -1

This is a simple linear system which I will not bother with in too much detail, so you'll just have to trust me when I say the solution is
A = 1/3, B=-1/3

The expanded integral, then, is

int (-du) / (u^2 + u - 2) = int 1/(3(u+2))du - int 1/(3(u-1))du

From here the answer should be fairly clear:

int (du)/(3(u+2)) - int (du)/(3(u-1)) = 1/3ln|u + 2| - 1/3ln|u - 1| + C

However, we must substitute u back to get our answer in terms of x. Our final answer then is

1/3 ln |cos x + 2| - 1/3 ln|cos x - 1|

After a small tweak for the sake of aesthetics:

1/3 ln|(cos x + 2)/(cos x - 1)|